Study of MDM2 and SUMO-1 expression in actinic cheilitis and lip cancer - Oliveira Alves, Monica Ghislaine [UNESP]; Delgado, Adriana da Mota [UNESP]; Balducci, Ivan [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Rodrigues Cavalcante, Ana Sueli [UNESP]; Almeida, Janete Dias [UNESP] (Springer, 2014)
Actinic cheilitis exhibits a potential of malignant transformation in 10-20 % of cases. The objective of this study was to compare the expression of MDM2 and SUMO-1 proteins between actinic cheilitis (AC) and squamous cell carcinoma (SCC) of the lip. The sample consisted of lower lip mucosa specimens obtained from cases with a clinical and histopathological diagnosis of AC (n = 26) and SCC (n = 25) and specimens of labial semi-mucosa (n = 15) without clinical alterations or inflammation. The tissue samples were stained with hematoxylin-eosin and anti-MDM2 and anti-SUMO-1 antibodies. Data were analyzed by the Kruskal-Wallis and Dunn's tests (5 %). The median expression of MDM2 (kW = 36.8565; df = 3-1 = 2; p = 0.0001) and SUMO-1 (kW = 32.7080; df = 3-1 = 2; p = 0.0001) was similar in cases of AC and SCC of the lip, but differed significantly from that observed for normal labial semi-mucosa. Despite the limitations of the present study, immunohistochemistry demonstrated the overexpression of important proteins (MDM2 and SUMO-1) related to regulatory mechanisms of apoptosis in AC and SCC of the lip, but further studies are needed.
Keywords: Actinic cheilitis; Squamous cell carcinoma; Immunohistochemistry; Proto-Oncogene Proteins c-mdm2; SUMO-1 protein